ADAPTASI KELUARGA IMIGRAN (PENGUNGSI) DI PEKANBARU (STUDI KASUS PENGUNGSI AFGHANISTAN) - ", Ulandary; Rosaliza, Mita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The score is submitted to qualify for a Strata 1 (S1) Sociology degree. With the title “ Immigrant (Refugee) Family Adaptation in Pekanbaru (Afghanistan Refugee Case Study) This research aimed the for communication process adaptation immigrant family in Pekanbaru, to describe habitus and to find out about the activity of immigrant family in Pekanbaru. In the reality of everyday life in society, it is realised that in society it’s many social backgrounds are either in adaptation or in communication. One in the immigrant family life in Pekanbaru. Adaptation is something to solve when a person or group of people communication with other cultural differences. Intercultural adaptation proces are an interactive process that develops through invader individual communication activity with it’s cultural social environment. The writing uses a descriptive qualitative method with two months of research. This data is in the bottom of the ninth with an interview with five informans purposive sampling. Findings shows that adaptation process between immigrant (refugees) and the local communities bagin by learning the language and speech codes of the local people. Then they communication formally and non formally with the surronding communication. The communication had not been effective because of language and cultural differences and so they found  it difficult to understand one another. Furthermore, in adaptation to a family of individualisme immigrants in which they only socialized with neighbors instead of the society around them.Key word: Immigrant (refugess), adaptation, habitus